ANALYSIS OF BELLE’S CHARACTER IN BEAUTY AND THE BEAST MOVIE (2017) DIRECTED BY BILL CONDON - Abdul Muhid Murtadho; Vionita Rizki Maharani (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
The objectives of this research are to find out the positive and negative character of Belle’s in Beauty and The Beast Movie directed 2017 by Bill Condon. The author used qualitative method for this thesis, the researcher watching the movie Beauty and The Beast and read the play script carefully. The aim of this thesis is to reminder to all women that positive character is should be implementation in the daily of life. From this movie there are have the positive value that can be implementation in our lives, Belle have positive character that can motivation us in our daily life there are brave, helpful, clever, loving and openminded. The positive character that Belle have is from her environment that Belle lives in village, seeing Belle different because her hobby is reading book not like the other young girls villager that have hobby is makeup. Keywords: positive character, social status, struggle based on character